THE ROLE OF EMOTIONAL INTELLIGENCE IN THE FORMATION OF STUDENTS’ CROSS-CULTURAL COMPETENCE: CHALLENGES OF GLOBALIZATION AND INTERCULTURAL COMMUNICATION - Косенчук, Юлія (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article presents a theoretical and empirical analysis of the role of emotional intelligence in the formation of students’ cross-cultural competence in the context of globalization and the intensification of intercultural communication. Modern scientific approaches to understanding emotional intelligence and intercultural competence are summarized; their structural components and psychological mechanisms of interrelation are outlined. The key psychological and social factors determining the effectiveness of intercultural interaction in the student environment are identified. The purpose of the study is to investigate the relationship between the level of emotional intelligence and the level of students’ cross-cultural competence, as well as to analyze effective methods for their development in the educational process. To achieve this goal, theoretical analysis of scientific sources, questionnaires and student surveys, training and interactive methods, as well as methods of statistical data processing, including correlation and comparative analysis, were used. The research results indicate that emotional intelligence acts as one of the leading factors in the formation of cross-cultural competence, as it facilitates the development of empathy, tolerance, emotional self-regulation, and behavioral adaptability in a multicultural environment. The effectiveness of using training programs, role-playing games, case studies, and reflective exercises to improve students' emotional intelligence and intercultural skills is substantiated. Conclusions. It is concluded that integrating the development of emotional intelligence into the educational programs of higher education institutions creates conditions for the systematic formation of cross-cultural competence and increases students' readiness for intercultural communication in the globalized educational space.